Attainment of Course Outcomes in Outcome Based Education:A Case Study - Balasubramani, R. (Journal of Engineering Education Transformations, 2016)
In the new Outcome Based Education model as prescribed by National Board of Accreditation (NBA), one of the most important criteria is the Attainment of Course Outcomes (COs). The Course Outcomes can be attained through several Direct and Indirect Assessments. This all can be achieved with clearly defining the Course Outcomes of the Course. In this paper, we have taken a Sample Course and we have clearly explained the methodology used in the assessment of attainment.